Profil Penggunaan Antibiotik untuk Pengobatan Pasien COVID-19 di Salah Satu Rumah Sakit Kota Bitung - Tampa'i, Randy; Lumepaa, Destine Daity; Mangangantung, Devita Kristianty Johana (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: The overuse and misuse of antibiotics during the COVID-19 pandemic is one of the biggest concern that needs attention, considering antimicrobioal resistance has been a major threat to global health. According to WHO, this condition can make the infection difficult to treat, increasing the risk of disease spread and mortality. The significant increase in the number of COVID-19 cases in North Sulawesi and the excessive use of antibiotics in COVID-19 patients, shows that research that aims to describe the use of antibiotics in COVID-19 is needed as an early detection of irrational use of antibiotics.Methods: This study was carried out in one of the COVID-19 Referral Hospital in the city of Bitung. The data of this study was collected by purposive sampling and conducted retrospectively. Sources of secondary data is from the patient medical records and patient treatment records. In this study 148 samples that meet the inclusion criteria are used. The inclusion criteria is hospitalized patients which is confirmed with COVID-19 during the period of July-December 2021, received antibiotic therapy during the treatment period, and medical record data.Result: The result shows that the mostly used antibiotics for COVID-19 theraphy are Azithromycin tablets 47.97% from the macrolide groups; Ceftriaxone injection 20.32% and Cefixime tablets 16.67% from the cephalosporin groups;  and Levofloxacin infusion 8.94% from the fluoroquinolones group.Conclusion : Patients at the productive age is most likely to get exposed with COVID-19. The clinical symptoms frequently occur in the mild category (68.92%). The use of antibiotics in COVID-19 patients at one of the COVID-19 Referral Hospitals in Bitung City is in accordance with the 3rd edition of the COVID-19 Management Guidelines, and the mostly used antibiotics is Azithromycin tablets as many as 118 patients (47.97%).